Greenhouse Gas Mitigation and Price-Driven Growth in a Solow-Swan Economy with an Environmental Limit - Michael C. Burda; Leopold Zessner-Spitzenberg (Institute of Labor Economics (IZA), 2024)
The existence of an environmental limit in the Solow-Swan economy changes the nature of economic growth, but does not preclude it. When atmospheric greenhouse gases reach a predetermined absolute threshold, further growth requires a permanently expanding, resource-intensive mitigation effort. If the rate of technical progress in mitigation is too low, it becomes the effective constraint on economic growth. Yet growth in both quantities and relative prices remains a robust feature of this class of economies. It also characterizes the social planner's optimum that anticipates the costs of reaching the environmental limit abruptly.
Keywords: O44; Q01; Q54; 330; Solow-Swan growth model; Baumol cost disease; anthropogenic climate change; mitigation; price-driven economic growth; Ramsey optimal policy